Distinct condensation droplet distribution patterns under low- and high-frequency electrowetting-on-dielectric (EWOD) effect. (1st November 2022) - Yan, Run; Cheng, Kai-Hao; Pham, Robin; Chen, Chung-Lung
Highlights: A multi-layer open-plate EWOD device was designed to serve as a condensing test surface. The electrode regions were designed to be grid patterns. Distinct droplet distribution patterns under various frequencies were investigated. Various droplet oscillating modes introduced intriguing mechanisms of droplet coalescence. Condensation rate can be enhanced with appropriate AC frequencies and sizes of electrode grid. Abstract: Distinct droplet distribution patterns of open-plate grid-wire-patterned EWOD devices under low (1 Hz, 5 Hz) and high (500 Hz, 1000 Hz) frequencies of AC-EWOD were discussed in this paper. Under low frequencies, droplets stayed inside the grid; under high frequencies, droplets adhered to the grid wires. Single droplet (1 μL) dynamics were studied with a discovery of contact-angle-fully-recover and contact-angle-partially-recover oscillation modes. These two modes induced distinct droplet coalescence mechanisms and distribution patterns. The natural response frequency was introduced to validate these two modes. Visualization experiments of droplet distribution were carried out on 0.5 mm, 1 mm, and 2 mm grid samples under 2 Hz, 50 Hz, 100 Hz, and 200 Hz. Condensate was collected to investigate the grid size (0.5 mm, 1 mm, 2 mm) and frequency effect (1 Hz, 100 Hz, 200 Hz) on condensation rate. Higher frequency demonstrated a larger condensation rate than the lower ones; the 1 mm grid samples showed more inspiring results compared with the 0.5 mm and 2 mm grid samples. EWOD provided an active and reversible way to interfere with droplet dynamics, and promote droplet growth and coalescence, which demonstrated great potential for future applications in droplet control and condensation enhancement.